Respostas

A melhor resposta!
2014-01-13T10:04:32-02:00
 f(x)=x²+8x+12
x²+8x+12=0
a= 1 b=8 c=12
Δ= (8)²-4·1·12
Δ= 64-48
Δ=16

x= -8+/- 
√16/2
x'= -8+/-4/2
x'=- 2
x''= -6

S:[-2,-6]

Alternativa D
1 5 1
2014-01-13T10:07:10-02:00
 x²+8x+12=0
a = 1
b = 8
c = 12

Δ = b²-4.a.c
Δ = 8²-4.1.12
Δ = 64 - 48
Δ = 16

x = (-b ± √Δ) / 2.a
x = (-8 ± √16) / 2.1

x' = (-8 + 4) / 2
x' = -4 / 2
x' = -2

x'' = (-8 - 4) / 2
x'' = -12 / 2
x'' = -6

Resposta é x' = -2 e x''= -6 alternativa D)

Espero ter ajudado. :)





1 4 1